A study of university students’ attitudes towards contemporary music in Guangxi Arts University in Nanning, China / Feng Yue - Feng , Yue (2017)
The purpose of this study was to investigate the students’ attitudes toward contemporary music in university. A sample of 100 music students from Guangxi Arts University in Nanning, China participated in this study. The survey designed for this study contained a set of questions that investigated on the students’ attitudes toward the contemporary music. The data analysis included descriptive statistics, T-test and analysis of variance (ANOVA) to evaluate the music students’ attitudes. In general, the findings revealed that the attitude scores did not differ significantly by gender and music courses that have been taken in university, but was found to differ significantly by music students’ years of music learning experience. Implications for contemporary music learning and research were discussed in this paper. Recommendations for further investigation were included.